Integrasi Literasi Keuangan dan Digital Marketing untuk Pemberdayaan UMKM Kuliner - Nasution, Minasari; Gani, Abdul; PS, Andry Roy; Fadli, Zahri; Mahyudin, Mahyudin; Khairina , Nurul (Ali Institute of Research and Publication, 2026)
This community service program aims to improve the competitiveness of culinary MSMEs in Siboruon Village through financial literacy and digital marketing education. This activity was attended by 35 participants and was carried out using participatory training and practical mentoring methods. Evaluation was conducted through pre-test and post-test questionnaires that were analyzed statistically. The results showed a significant increase in financial literacy scores, from an average of 2.48 to 4.21 (p < 0.001), as well as digital marketing competencies, from an average of 2.10 to 4.03 (p < 0.001). A total of 71.4% of participants successfully created or optimized business social media accounts. The novelty of this program lies in the integration of simple bookkeeping and platform-based digital marketing tailored to the characteristics of rural MSMEs. This program has proven to be effective in strengthening managerial capacity and increasing the competitiveness of MSMEs.